1989
DOI: 10.2136/sssaj1989.03615995005300030035x
|View full text |Cite
|
Sign up to set email alerts
|

Gypsum Occurrence in Soils on the Margin of Semipermanent Prairie Pothole Wetlands

Abstract: A series of three wetlands in a local recharge‐throughflow‐discharge groundwater flow system were investigated to determine factors controlling concentration of gypsum at the wetland edge. The three wetlands differ in pond size, permanence, salinity, and in their relationship to the groundwater hydrology. We believe gypsum accumulation resulted from long term hydrologic, geomorphic, and climatic factors. Wetland salinity appeared to control the distribution and amount of gypsum in soils around individual wetla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Thus, the present data do not indicate a strong tendency to supersaturation, in agreement with results of other investigations (Friedel, 1978;Steinwand and Richardson, 1989) in which it was observed that the tendency to supersaturation with respect to gypsum is much weaker than that with respect to calcite. For the ratio IAP/Ksp for calcite in soil solutions, Inskeep and Bloom (1986b) found values as high as 40.…”
Section: Supersaturation Soil Solutions With Gypsum 69supporting
confidence: 93%
“…Thus, the present data do not indicate a strong tendency to supersaturation, in agreement with results of other investigations (Friedel, 1978;Steinwand and Richardson, 1989) in which it was observed that the tendency to supersaturation with respect to gypsum is much weaker than that with respect to calcite. For the ratio IAP/Ksp for calcite in soil solutions, Inskeep and Bloom (1986b) found values as high as 40.…”
Section: Supersaturation Soil Solutions With Gypsum 69supporting
confidence: 93%
“…Carbonate distribution is influenced by hydrology, and in general carbonates were nearest the surface where soils were inundated or had a water table within 30 cm of the surface (Figure 3). Steinward and Richardson (1989) found that gypsum also precipitated around the edges Minimum of prairie potholes wetlands that were seasonally ponded.…”
Section: Soil and Water Characteristicsmentioning
confidence: 99%
“…This has begun to move us beyond a bstaticQ treatment of catenas by infusing the dynamic aspect of water flowing laterally through soil (hydrosequences). Pedon morphology can be placed within a threedimensional context that explains differential concentrations across a landscape (Park and Burt, 1999;Steinwand and Richardson, 1989;Wysocki and Schoeneberger, 2000). For example, the association of increased manganese concentrations with wetter portions of a hilly landscape (e.g., McDaniel and Buol, 1991;McDaniel et al, 1992) is an example of migration and concentration of specific soil constituents facilitated by lateral internal water movement.…”
Section: Soil Morphology and Soil Geographymentioning
confidence: 99%